Analysis on Clarity of Rubies Gemstones Using Charge-Coupled Device (CCD) - Fatinah Mohd Rahalim; Syarfa Najihah Raisin; Irneza Ismail; Yasmin Abdul Wahab; Ruzairi Abdul Rahim; Mus'ab Sahrim; Sharma Rao Balakrishnan; Wan Zakiah Wan Ismail; Farah Aina Jamal Mohamad; Nur Arina Hazwani Samsun Zaini; Juliza Jamaludin (MyCT Publishers, 2024)
Non-Indexed Publication